GREEN MARKETING, PENGETAHUAN DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK BENING’S DI ROSI STORE SOLOK-SELATAN - Wulan Rahmadani; Maria Magdalena (Jurnal Bina Bangsa Ekonomika, 2024)
Based on the formulation of the problem in this study is whether green marketing affects purchasing decisions on clear cosmetics's at rosi store South Solok, whether knowledge affects purchasing decisions on clear cosmetics's at rosi store South Solok and. Through the sample questionnaire method using the slovin formula, there were 85 respondents. Does trust affect the purchase decision on clear cosmetics's at Rosi store South Solok? Through the sample questionnaire method using the slovin formula, there were 85 respondents.with the sampling used in this study is probability sampling. By using instrument test testing, validity test and reality test, descriptive test, classical assumption test, normality test, multicollinearity test and heteroschidasticity test, then multiple linear regression and hypothesis test with the help of SPSS application. The results of the study show that green marketing  has a positive and significant effect on purchasing decisions on clear cosmetics's at rosi store South Solok, knowledge has a positive and significant effect on purchasing decisions on clear cosmetics's at rosi store South Solok and  trust has a positive and significant effect on purchasing decisions on clear cosmetics's at rosi store South Solok. So it can be concluded in this study found that green marketing variables, knowledge and trust have a positive and significant effect on purchasing decisions on clear cosmetics's at Rosi store South Solok. Where the calculated t value is greater than the table t